The politics of Palestinian multilingualism: Speaking for citizenship - Hawker, N (Routledge, 2019)
The Politics of Palestinian Multilingualism: Speaking for Citizenship provides an essential contribution to understanding the politics of Israel/Palestine through the prism of sociolinguistics and discourse analysis. Arabic-speakers who also know Hebrew resort to a range of communicative strategies for their political ideas to be heard: they either accommodate or resist the Israeli institutional suppression of Arabic. They also codeswitch and borrow from Hebrew as well as from Arabic registers and styles in order to mobilise discursive authority. On political and cultural stages, multilingual Palestinian politicians and artists challenge the existing political structures. In the late capitalist market, language skills are re-packaged as commodified resources. With new evidence from recent and historical discourse, this book is about how speakers of a marginalised, contained language engage with the political system in the idioms at their disposal.